Work-life balance practices and employee job satisfaction: A case study of Ghana's security industry in Greater Accra - Amegayibor, Godson Kwame (Goodwood Publishing, 2023)
Purpose: The main goal of this study is to determine how work-life balance factors influence employees' job satisfaction in the security sector. Research Methodology: To sample 115 employees, a quantitative methodology and correlational descriptive design, as well as a census technique, were used. The data were collected using structured questionnaires. The hypotheses were tested using multiple linear regression, and the data were input, processed, and analyzed using SPSS version 20. Results: The findings showed that employees benefit from the organization's work-life balance strategies developed to guarantee that work life is easy for all employees. It also highlighted that several work-life balance elements have a substantial influence on employees' job satisfaction. Limitations: A drawback is that, especially in Ghana's security industry, work-life balance practice has received less attention in the management literature. The study was limited in scope and concentrated on two districts in an urban environment. Contribution: This theory supports the notion that elements of work-life balance influence job satisfaction. Whatever occurred or Any effort made to support employees’ work life would produce definite results when these factors or practices are ingrained into the security service and other organizations’ general policies and programs. This amply demonstrates the importance of work-life balance as a pivot point for employees' ability to meet organizational goals. It is good that the human resource management of every organization pays critical attention to these factors because they will increase job satisfaction and enhance performance.